Effects of B-cell directed therapy on the preclinical stage of rheumatoid arthritis: the PRAIRI study. Issue 2 (9th February 2019) - Gerlag, Danielle M; Safy, Mary; Maijer, Karen I; Tang, Man Wai; Tas, Sander W; Starmans-Kool, Mirian J F; van Tubergen, Astrid; Janssen, Matthijs; de Hair, Maria; Hansson, Monika; de Vries, Niek; Zwinderman, Aeilko H; et al.
Abstract : Objectives: We explored the effects of B-cell directed therapy in subjects at risk of developing autoantibodypositive rheumatoid arthritis (RA), who never experienced inflammatory arthritis before, and explored biomarkers predictive of arthritis development. Methods: Individuals positive for both anti-citrullinated peptide antibodies and rheumatoid factor but without arthritis were included in a randomised, double-blind, placebo-controlled study to receive a single infusion of 1000 mg rituximab or placebo. Results: Eighty-one individuals received treatment and were followed up for a mean of 29.0 (0–54) months, during which 30/81 (37%) individuals developed arthritis. The observed risk of developing arthritis in the placebo-treated group was 40%, which was decreased by 55% (HR 0.45, 95% CI 0.154 to 1.322) in the rituximab-treated group at 12 months. Rituximab treatment caused a delay in arthritis development of 12 months compared with placebo treatment at the point when 25% of the subjects had developed arthritis (p<0.0001). Erythrocyte sedimentation rate and the presence of anti-citrullinated α-enolase peptide 1 at baseline were significant predictors of arthritis development. Conclusions: A single infusion of 1000 mg rituximab significantly delays the development of arthritis in subjects at risk of developing RA, providing evidence for the pathogenetic role of B cells in the earliest, prearthritis stage of autoantibody positive RA.